Aktivitas Orangutan Tapanuli (Pongo tapanuliensis) Berdasarkan Pergerakan, Posisi Tubuh, dan Penggunaan Strata Hutan - Tazkiah, Citra; Hutasuhut, Melfa Aisyah; Manalu, Kartika (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to identify the number of individuals and describe the daily behavior, movements, body position, and forest strata preferences of Tapanuli orangutans (Pongo tapanuliensis) at Camp Mayang Batang Toru Research Station, North Sumatra. This study used the focal animal sampling method and data collection techniques were carried out through direct observation with binoculars of daily activities carried out on target orangutans. This research was conducted from October 2023 to March 2024. Data analysis was carried out by descriptive statistics of the frequency of orangutan behavior based on activities carried out at Camp Mayang Station, Batang Toru, North Tapanuli, North Sumatra and presented in the form of tables and figures and then explained in the form of diagrams or graphs. The results of this study showed that there were 3 individual Tapanuli orangutans (Pongo tapanuliensis), namely Cemara, Beta, and Bittang. Daily activities observed included eating, moving, resting and other activities. Frequent movement activities were hanging up, walking on two legs and descending. Body positions that orangutans often do are Sitting, Squatting and Standing on two legs or one leg Forest stratum level 3 is more frequently used by orangutans than forest stratum level 4.